2006
DOI: 10.1093/ps/85.5.947
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate Statistical Methods to Compare Dose Responses of Methionine Sources

Abstract: Two sources of methionine (Met) activity are frequently used in commercial feed formulation: DL-2-hydroxy-4-(methylthio) butanoic acid (HMTBA), most commonly available as an 88% solution with 12% water; and DL-methionine (DLM, 99% powder). Despite the fact that both compounds have been in commercial use for over 50 yr, controversy and confusion remain with respect to their relative bioefficacy (RBE). This paper presents a review of the use of a nonlinear common plateau asymptotic regression technique (NLCPAR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 15 publications
0
37
1
1
Order By: Relevance
“…Тварині не потрібно витрачати додаткові життєві ресурси та енергії для переведення частини D-метіоніну в L-метіонін. Виходячи з отриманих в ході досліджень даних (Jiao et al, 2010;Kratzer, Littell, 2006;Kubińska et al, 2014;Liu et al, 2010;Mitchell, Lemme, 2008;Narayanswamy, Bhagwat, 2010;Paulicks et al, 2009;Sangali et al, 2014;Vazquez-Anon et al, 2006;Yi et al, 2007), очевидно, що джерела метіоніну мають різну ефективність. Тому метою наших досліджень було визначити вплив різних джерел метіоніну у комбікормах на продуктивність та забійні якості перепелів м'ясного напряму продуктивності.…”
Section: вступunclassified
“…Тварині не потрібно витрачати додаткові життєві ресурси та енергії для переведення частини D-метіоніну в L-метіонін. Виходячи з отриманих в ході досліджень даних (Jiao et al, 2010;Kratzer, Littell, 2006;Kubińska et al, 2014;Liu et al, 2010;Mitchell, Lemme, 2008;Narayanswamy, Bhagwat, 2010;Paulicks et al, 2009;Sangali et al, 2014;Vazquez-Anon et al, 2006;Yi et al, 2007), очевидно, що джерела метіоніну мають різну ефективність. Тому метою наших досліджень було визначити вплив різних джерел метіоніну у комбікормах на продуктивність та забійні якості перепелів м'ясного напряму продуктивності.…”
Section: вступunclassified
“…This assumption has been questioned by Kratzer and Littell (2006) who suggested to use two separate models (with diff erent asymptotes) when comparing DLM and MHA availability. In contrast, Piepho (2006) considered the conclusions by Kratzer and Littell (2006) not fully justifi ed from a statistical point of view.…”
Section: Treatmentmentioning
confidence: 99%
“…This assumption has been questioned by Kratzer and Littell (2006) who suggested to use two separate models (with diff erent asymptotes) when comparing DLM and MHA availability. In contrast, Piepho (2006) considered the conclusions by Kratzer and Littell (2006) not fully justifi ed from a statistical point of view. To confront these two approaches, separate exponential models were fi tted to carcass and breast meat yield data (recalculated to equimolar basis) obtained in the present study as suggested by Kratzer and Littell (2006).…”
Section: Treatmentmentioning
confidence: 99%
“…Furthermore, the correct statistical design to evaluate the bioavailability of different sources of essential nutrients has been under debate (Littell et al, 1997;Kratzer and Littell, 2006;Piepho, 2006). A standardized method of statistical analysis would make comparisons of experiments assessing different sources of nutrients easier and more accurate (Littell et al, 1997).…”
Section: Introductionmentioning
confidence: 99%